Supply Chain Model for Three-Echelon Supply Chain for Perishable Products - Oberoi, Sarbjit Singh; Tripathy, Bibhuti Bhusan (STIE Malangkucecwara, 2024)
This paper proposed three echelon supply chain models. In this study, we have considered that after production, the manufacturer supplies the perishable items to the supplier, and then the retailer receives the product from the supplier for sale to the customers. The retailer assumes the customer’s seasonal demand along with the supplier’s uncertain lead time. In this model, the product expiration date is also considered. The model helps the complete supply stakeholders to optimize their profits by managing optimal inventory.